A general approach to shape characterisation for biomedical problems. (15th April 2008) - Moroni, Davide; Perner, Petra; Salvetti, Ovidio
In this paper, we present a general approach to shape characterisation and deformation analysis of 2D/3D deformable visual objects. In particular, we define a reference dynamic model, encoding morphological and functional properties of an objects class, capable of analysing different scenarios in heart left ventricle analysis. The proposed approach is suitable for generalisation to the analysis of periodically deforming anatomical structures, where it could provide useful support in medical diagnosis. Preliminary results in heart left ventricle analysis are discussed.